Oxalis corniculata and Ficus religiosa mitigates rotenone-induced Parkinson’s disease in Swiss Albino mice: Mechanistic insights and therapeutic potential - Praveen Kumar, Himanshu Sachdeva, Sunishtha Kalra, Balwan Singh, Ram Dayal, Govind Singh (Journal of Applied Pharmaceutical Science, 2024)
Parkinson’s disease (PD) is a neurodegenerative disorder distinguished by the presence of progressive deterioration of the nervous system and is prevalent among the elderly population. The pathological hallmark of PD involves the accumulation of the protein alpha-synuclein and neuronal inflammation, which leads to the degeneration of dopaminergic (DAergic) neurons. In the present study, neuroprotective effect of combinational extract of Ficus religiosa (F. religiosa) and Oxalis corniculata (O. corniculata) L. in a mouse PD model. By giving Rotenone (ROT) on alternate days subcutaneously for 21 days, a disease model was generated. Extracts were administered individually as well as in combination orally 1 hour before ROT (1.5 mg/kg, s.c.) administration. On day 22nd, after sacrificing of animals neurochemical assays [total protein content (TPC), malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), nitrite (NO)], neurotransmitter analysis, and histology of the brain were performed. Results of the study showed a significant increase in the level of TPC, CAT, SOD, GSH, and dopamine in substantia nigra and a significant reduction of MDA, NO, and glutamate after administration of F. religiosa and O. corniculata in combination (200 + 500 mg/kg, p.o.) in a ROT induced model. This study demonstrated that a combination of F. religiosa and O. corniculata improved motor symptoms and reduced dopaminergic neuron death in mice challenged with ROT.
Keywords: Alfa-synuclein, Ficus religiosa, neuroprotective, Oxalis corniculata, parkinson’s disease, rotenone